(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The magnificent epic The Valmiki Ramayana gives advice on how to live a good life at eachstage of life. Various tough events arise in a person’s life, and the Valmiki Ramayana demonstrates how tonavigate through them pleasantly and effortlessly. Lord Rama and Goddess Sita present an ideal fordealing with many forms of clashing situations and living a happy and healthy life in the ValmikiRamayana. Furthermore, their actions and lifestyles represent a variety of values, including moral,spiritual, intellectual, artistic, cultural, and other values that help us construct a healthier and bettersociety. Ramayn is an epic that serves as a basis for establishing values throughout the world for theperiod. Satyuga, Dwapryuga, Tretayuga, and Kalyuga are the four ages that largely contribute to societalevolution in the epic of Ramayan.